Random insertion transposon mutagenesis of Mycobacterium fortuitum identified mutant defective in biofilm formation - Katoch, Poonam; Gupta, Kinam; Yennamalli, Ragothaman M.; Vashistt, Jitendraa; Bisht, Gopal Singh; Shrivastava, Rahul (Biochemical and biophysical research communications, 2020)
Mycobacterium fortuitum has emerged as a nosocomial infectious agent and biofilm formation attributed for the presence of this bacterium in hospital environment. Transposon random mutagenesis was used to identify membrane-proteins for biofilm formation in M. fortuitum. Ten mutants were shortlisted from a library of 450 mutants for examine their biofilm forming ability. Comparative biofilm ability with respect to wild type M. fortuitum ATCC 6841 showed an altered and delayed biofilm formation in one mutant namely, MT721. Sequence analysis revealed mutation in anthranilate phosphoribosyl transferase (MftrpD), which is associated with tryptophan operon. Functional interaction study of TrpD protein through STRING showed its interaction with chorismate utilizing proteins, majorly involved in synthesis of aromatic amino acid and folic acid, suggesting that biofilm establishment and maintenance requires components of central metabolism. Our study indicates important role of MftrpD in establishment and maintenance of biofilm by M. fortuitum, which may further be explored for drug discovery studies against mycobacterial infections.